Building a Revisit Intention Model of Independent Tourism Villages in Bali - Jodi, I Wayan Gede Antok Setiawan; Sukawati, Tjokorda Gde Raka; Sukaatmadja, I Putu Gde; Suasana, I Gusti Agung Ketut gede (Journal of Posthumanism, 2025)
Tourism visits in Bali, especially in independent tourism villages, are still low compared to the number of visits before the pandemic, so it is necessary to encourage tourism to maintain it, one of which is by encouraging revisit intention. The purpose of this study is to explain the influence of destination image (based on THK), service quality, tourism experience, government policy on revisit intention.The Grand Theory in this study is the Theory of Planned Behaviour with Supporting Theory SOR and Resource Based View (RBV). The study was conducted on independent category tourist villages in Bali, with a sample size of 220 respondents based on a purposive sampling approach. The research respondents were people who had or were visiting tourist villages in Bali. Data were collected offline, namely directly distributed to each respondent. The collected data were analysed using Smart-PLS.The results show that Destination image (based on THK) and service quality have a positive and significant effect on revisit intention, destination image (based on THK) and service quality have a positive and significant effect on tourism experience, tourism experience has a positive and significant effect on revisit intention, tourism experience mediates the influence of destination image (based on THK) and service quality on revisit intention, government policy is unable to moderate the influence of Destination image (based on THK) on revisit intention and finally government policy moderates quasi-moderation the influence of service quality on Revisit Intention. This study is able to build and prove the revisit intention model using TPB Theory, SOR Theory. the results of the study showed that the tourism experience variable which was proven to be a partial mediation variable. Therefore, the managers of Independent Tourism Villages can take concrete steps to increase revisit intention.